2022
DOI: 10.2147/ijn.s380810
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Hearing Loss in Ototoxic Mouse Model Through SPIONs and Dexamethasone-Loaded PLGA Nanoparticle Delivery by Magnetic Attraction

Abstract: Background Ototoxicity currently has no available treatment other than medication withdrawal as soon as toxicity is suspected. The human inner ear organs have little potential for regeneration; thus, ototoxicity-induced hair cell injury is deemed permanent. Dexamethasone (Dexa) is a synthetic steroid analog that has significant potential for otoprotection in the treatment of various inner ear diseases; however, its low absorption into the inner ear prevents significant recovery of function. Nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Cheng and Wei showed that therapeutic FAH mRNA delivered by dendrimer‐based lipid NPs normalizes liver function and lengthens survival, via a mouse model of hepatorenal tyrosinemia type I 330 . In an ototoxic mouse model, researchers discovered that dexamethasone‐loaded PLGA NPs delivered by magnetic attraction can prevent hearing loss 368 . Using a mouse model of collagen‐induced arthritis and a human transgenic mouse model of arthritis, Zhang et al 369 .…”
Section: Evaluation Models Of Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng and Wei showed that therapeutic FAH mRNA delivered by dendrimer‐based lipid NPs normalizes liver function and lengthens survival, via a mouse model of hepatorenal tyrosinemia type I 330 . In an ototoxic mouse model, researchers discovered that dexamethasone‐loaded PLGA NPs delivered by magnetic attraction can prevent hearing loss 368 . Using a mouse model of collagen‐induced arthritis and a human transgenic mouse model of arthritis, Zhang et al 369 .…”
Section: Evaluation Models Of Npsmentioning
confidence: 99%
“…330 In an ototoxic mouse model, researchers discovered that dexamethasone-loaded PLGA NPs delivered by magnetic attraction can prevent hearing loss. 368 Using a mouse model of collagen-induced arthritis and a human transgenic mouse model of arthritis, Zhang et al 369 discovered that neutrophil membrane-coated NPs exhibit significant therapeutic efficacy by reducing joint destruction and the severity of arthritis as a whole. There are also studies that examined the antipsoriatic and toxic effects of methotrexate-loaded chitin nanogels in an imiquimod (IMQ)-induced mouse model, and they discovered that they were an ideal delivery platform for topical methotrexate delivery in psoriasis due to their significant antipsoriatic efficacy on IMQ-induced model of psoriasis without any dermal and systemic toxicities.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation